KSA The Influence of Mother Tongue Interference on the Translation Process - Elnour Hadi (Journal of Arabic Education and Linguistic, 2023)
This paper aims to investigate the problems of translation encountered by ESL learners when translating texts i-e English to Arabic language and vice versa. Translation problems can be divided into linguistic problems and cultural problems. The solutions proposed to translation problems are based on the types of text, the minor linguistic context, possibility of saying something in the target Language. Some considerations follow this process, which is mainly related to the accuracy, clarity, and naturalness of the meaning, ideas, or messages of the translation. Knowledge of the target culture is crucial for successful translation. To understand this interference in detail, the research shed the light on this problem. The research deals with the significance of the study in the field of second language learning and theoretical reviews of second language acquisition. The researcher used a specific methodology in this study to discuss the collected data and analyze it statistically to reach the main findings in the conclusion.